PROSES DESAIN KOMUNIKASI VISUAL IKLAN POLITIK DALAM PILKADA MOROWALI TAHUN 2012 - Achmad Herman; Anita Pahlevi; Yulianti Said (Kanal: Jurnal Ilmu Komunikasi, 2015)
The purpose of this study was to discuss visual communication design process of of political advertisement in the Morowali election 2012. This research method used a qualitative approach with descriptive research. This research subject is chosen by purposive sampling, each people from each candidate and data collection techniques used in-depth interviews and documentation. Ideally, in the process of visual communication design used seven stages, namely inspiration, identification, conceptualization, definition, exploration, communication, and production. The results showed that the campaign team of four candidates in the process of visual communication design political advertising did seven stages. However, in practice some stage wasn't taken maximum yet namely conceptualization, definition and production, due to the successful teams of the four candidates did not understand very well how the process of visual communication design.